1 Origins of neuropsychiatry/bnpa. Issue 8 (13th July 2017) - Bird, Jonathan
Abstract : As we leave the "Decade of the Brain" neuropsychiatry has emerged as one of the most exciting and challenging fields in which to work. The BNPA was founded in December 1987 at the suggestion of Dr Jonathan Bird. Professor W A Lishman, the founding Chairman, describes its formation as follows: "The Association was created to provide a forum for cross-disciplinary discussion of matters of common interest among psychiatrists, neurologists, neuropsychologists and workers in the related neurosciences. All suitably qualified persons with an interest in brain function in relation to behaviour would be welcome to join. For this reason, we did not seek formal affiliation with other bodies, such as the Royal College of Psychiatrists, but decided to stand as an independent association. Young members bringing fresh ideas would be particularly encouraged to join, by keeping fees to a minimum and the establishment of appropriate prizes". At the 2015 AGM Dr Jonathan Bird was awarded an honorary fellowship of the BNPA. Jonathan's fellowship was proposed by Professor Alwyn Lishman (Honorary Life President) who hoped the BNPA would recognise Jonathan's "sustained work and service over many years in the promotion of present day neuropsychiatry". In his commendation, he revealed that it was in fact Jonathan who first to suggested, to a group of like-minded colleagues, including Alwyn himself, the formation of the BNPA. Jonathan went on to serve as the secretary throughout its early years. The ability to bring people together towards common goals has continued and Jonathan was instrumental in forming the Section of Neuropsychiatry at The Royal College of Psychiatrists, and then serving as its first chair. He helped, although ably assisted by Dr Rafey Faruqui who succeeded him as chair, in guiding the nascent section through to the establishment of the status of Faculty, which is a major step forward as a mechanism for improving services and the development of recognised training. Jonathan originally read medicine at the University of Bristol, where he achieved the Prize for Physiology and did his junior training in the region. He went on to the Maudsley Hospital for his higher training, winning the prestigious Gaskell medal of the Royal College of Psychiatrists. He then worked as Clinical fellow at McMaster and was exposed to many of their revolutionary teaching approaches before returning to the Maudsley and then completing the circle with a return to Bristol to take up a consultant post at Burden Centre for Neuropsychiatry, Neuropsychology and Epileptology, Frenchay Hospital, Bristol. He has been active throughout his consultant career in Epilepsy Action and served as Chairman of their Professional Advisory Panel.